2011
DOI: 10.1002/app.34364
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel polyurethane acrylates based on soy polyols

Abstract: Novel polyurethane acrylates (PUAs) were prepared by the reaction of soy polyols with isophorone diisocyanate and hydroxyethylacrylate. FTIR results confirmed the formation of PUAs from different kinds of soy polyols. The glass transition, damping properties, thermal stabilities, and mechanical properties of PUAs were characterized by differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), thermogravimetric analysis (TGA), and universal test machine. The morphology of PUAs was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…However, in our case, the addition of ATT to the EA improved both the strength and toughness. Similar results were reported for other ATT/polymer composites . Wang et al .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, in our case, the addition of ATT to the EA improved both the strength and toughness. Similar results were reported for other ATT/polymer composites . Wang et al .…”
Section: Resultssupporting
confidence: 89%
“…showed that the nonmetric dispersion of ATT in the polymer matrix led to the improved modulus and strength. In this study, the tensile strength and toughness increase in the presence of ATT also directly benefitted from the reinforcement provided by the well‐dispersed ATT interfacial interaction between ATT and EA . As for the high‐ATT‐loading composites, the formation of agglomerates, as the SEM images show [Figure (e,f)], resulted in the fact that the ATTs could not act efficiently to dissipate the mechanical energy and instead served as flaws or defects and crack‐initiation sites .…”
Section: Resultsmentioning
confidence: 73%
“…First, urethane bonds as well as chain segments of polyols decompose to form volatile products such as carbon dioxide. Second, the oxidative decomposition of isocyanates compound takes place [3,29]. The TG and DTG curves for all nanocomposites indicate that there are also two main stages of thermal degradation.…”
Section: Thermal Stabilitymentioning
confidence: 98%
“…And the vegetable oils are considered to be one of the cheapest and most abundant biological sources available. Due to the specific structures and abundance, these vegetable oils have become an attractive resource that can convert to bio-based polyols to produce PUs [3][4][5][6][7]. Polyurethanes are a class of versatile polymers that have widely employed in coating, adhesive, foam, elastomer, composite, and biomedical materials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The polyols used in PUD synthesis are polyether, polyester and polycarbonate. However, vegetable oils have become attractive for the synthesis of PUDs because of their economical benefits and the fact that they are made from renewable resources [18][19][20][21][22][23]. CO is one of the vegetable oils that used as polyol in the synthesis of PU due to its cheapness and availability as renewable material [24][25][26].…”
Section: Introductionmentioning
confidence: 99%